Impact of improved stove intervention on infant acute respiratory infections: Results from a randomized trial in Northwest Ethiopia - Habtamu Demelash Enyew; Abebe Beyene Hailu; Seid Tiku Mereta (PLoS ONE, 2026)
Background Globally, millions of young children affected by acute respiratory infections every year, which is the leading cause of death and serious illness among children. Though strategies, including promoting improved stoves, have been implemented to combat this public health challenge, the effectiveness of local improved stoves introduced during pregnancy in reducing household air pollution and related respiratory illnesses remains limited. Method Following the main trial randomization, 343 infants born to mothers in the study groups were followed for six months, with assessments of acute respiratory infections (ARI) occurring every two months. The stove intervention’s impact was evaluated by comparing the acute respiratory infection incidence rate between the intervention and control groups. Respiratory illnesses were assessed using Integrated Management of Childhood Illness (IMCI) guidelines. The incidence rate ratio (IRR) was estimated using a marginal Poisson model fitted via Generalized Estimating Equations (GEE). Result During the six-month follow-up period, a total of 43 infants (18 intervention, 25 control) experienced at least one acute respiratory infection (ARI) episode, resulting in a cumulative incidence of 12% (95% CI: 10, 14%). Although the intervention group consistently showed a reduction in ARI incidence rates compared to the control group (a 20% reduction), the adjusted Incidence Rate Ratio (IRR = 0.81; 95%CI: 0.56, 1.16; P = 0.252) was not statistically significant. A non-significant trend toward benefit was noted overall, with the subgroup analyses suggesting promising, non-significant reductions primarily among female infants and infants from larger families. Conclusion The overall study did not find a statistically significant protective effect of the intervention stoves on ARI incidence. However, the observed non-significant trend suggests a potential protective effect. Further research with larger sample sizes and longer follow-up periods is warranted to confirm this potential benefit. Trial registration The main trial was registered at the Pan African Clinical Trial Registry website under the code PACTR202111534227089, ( https://pactr.samrc.ac.za/ (Identifier) on the registration date of (11/11/2021).